Review of Modern Three-Dimensional Integration Technologies and Analysis of Prospects of Their Use for High Power Micro-Assemblies - A.V. Sukhanov; A.I Artemova; R.S Litvinenko (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The new miniaturization technologies of electronic devices find extensive application in the design for any industry, whether it is civil electronics or appliances designed to operate in harsh environments. This article presents an overview of prospective technologies of three-dimensional integration at substrates level for use in the field of power electronics. The review describes the basic principles of three-dimensional integration technologies, their applicability for manufacturing electronic devices, the main advantages and disadvantages.